IMPLEMENTASI KEBIJAKAN PEMBERIAN IZIN USAHA PERTAMBANGAN GALIAN GOLONGAN C DI KABUPATEN KOLAKA - Suriani, Suriani; Parawu, Hafiz Elfiansyah; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research was conducted to determine the Implementation of the Policy for Granting Group C Quarry Mining Business Permits in Kolaka Regency. The method used in this research is qualitative research where this research is descriptive qualitative. Data collection techniques use data triangulation with observation, interview and documentation methods. The results of this study indicate that, Group C Excavation Mining in Kolaka Regency in the implementation of the policy of granting mining business permits, seen from environmental conditions, has not been good enough in its implementation. The relationship factor between organizations in this case is that the Central Government and Regional Governments are less effective in carrying out the implementation of the policy of granting class c excavation mining business permits. directly is the Regional Government. Furthermore, on the character factor of the implementor institute, namely the Head of Service or the executing agent has carried out his duties properly in implementing the granting of mining business permits, especially group c excavation